PENDIDIKAN KARAKTER DI SMK MUHAMMADIYAH SAMPIT - Novianti Rahmawati; M. Qahfi; Ilham Budi Prakoso (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2019)
This study aims to determine the factors that hinder the implementation of character education at the Muhammadiyah Vocational School Sampit in the 2018/2019 academic year. This study included qualitative descriptive research.The subjects in this study were teachers of the Muhammadiyah Sampit Vocational School in the 2018/2019 academic year, totaling five teachers. The method used in this study is an unstructured interview method. The validity of the data used is source triangulation.The results of this study indicate that the factors that hinder the implementation of character education at Muhammadiyah Sampit Vocational School are ignorant of parents of 5 respondents, negative mass media as many as 4 respondents, and a crisis of exemplary leaders and leaders of 3 respondents.